2013
DOI: 10.1124/mol.112.084616
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That Cytochromeb5and Cytochromeb5Reductase Can Act as Sole Electron Donors to the Hepatic Cytochrome P450 System

Abstract: We previously described the development of genetic models to study the in vivo functions of the hepatic cytochrome P450 (P450) system, through the hepatic deletion of either cytochrome P450 oxidoreductase [POR; HRN (hepatic reductase null) line] or cytochrome b 5 [HBN (hepatic cytochrome b 5 null) line]. However, HRN mice still exhibit low levels of mono-oxygenase activity in spite of the absence of detectable reductase protein. To investigate whether this is because cytochrome b 5 and cytochrome b 5 reductase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 40 publications
(62 reference statements)
6
50
0
Order By: Relevance
“…Deletion of Cyb5 in the HBN line upregulated hepatic Cyp2b10 and Cyp3a expression (Finn et al, 2008;Henderson et al, 2013); this trait was also apparent in the humanized HBN models (for those murine genes which had not been deleted) and CYP3A4 expression in humanized mouse liver was also increased by Cyb5 deletion. Conversely, deletion of hepatic Cyb5 in the CYP2D6 line reduced basal CYP2D6 expression in male, but not female, mice.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Deletion of Cyb5 in the HBN line upregulated hepatic Cyp2b10 and Cyp3a expression (Finn et al, 2008;Henderson et al, 2013); this trait was also apparent in the humanized HBN models (for those murine genes which had not been deleted) and CYP3A4 expression in humanized mouse liver was also increased by Cyb5 deletion. Conversely, deletion of hepatic Cyb5 in the CYP2D6 line reduced basal CYP2D6 expression in male, but not female, mice.…”
Section: Discussionmentioning
confidence: 87%
“…Since that time, numerous in vitro studies have confirmed this important function (Yamazaki et al, 1996(Yamazaki et al, , 2002Lamb et al, 2001;Yamaori et al, 2003;Akhtar et al, 2005). To establish the in vivo relevance of these findings, we recently undertook conditional deletion of Cyb5 in the mouse, demonstrating marked changes in the pharmacokinetics of a number of murine P450 substrates (Finn et al, 2008;Henderson et al, 2013Henderson et al, , 2014aMcLaughlin et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…We have not rigorously excluded the possibility of compensatory up-regulation of other reductases such as the cytochrome b 5 /cytochrome b 5 reductase system, which is partially redundant with POR in relation to one-electron reduction of cytochrome P450s (62). The high FSL-61 reductase activity of S3 and its derived clones could reflect such a change in gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas CPR deletion was found, as expected, to have a significant effect on P450 activity both in vitro and in vivo, we also demonstrated, for the first time in vivo, that b 5 deletion had a profound effect on P450 drug metabolism in a tissue-and substrate-dependent manner (Finn et al, 2008(Finn et al, , 2011McLaughlin et al, 2010). Furthermore, investigation of a residual P450 activity (;10%) in vitro in HRN samples through the generation of a mouse line in which both CPR and b 5 were deleted in the liver (hepatic b 5 reductase null) led us to demonstrate that b 5 -Cyb5R can act as sole electron donors to the P450 system both in vitro and in vivo (Henderson et al, 2013).…”
Section: Steroidogenic Cytochrome P450 17a1 Interactions With Catalyticmentioning
confidence: 99%